Worldview, psychological flexibility, and depression-anxiety-stress in Chinese youth - Cheng, Sheng-Li; Zhang, Xin; Zhao, Chenxu; Li, Yun; Liu, Shushan; Cheng, Sanyin (Frontiers in Psychology, 2024)
Background The psychological problems among the youth population have received widespread attention in the information age. However, little research has been conducted on the effects and mechanisms of worldview on depression, anxiety, and stress (DAS) among youth. In this study, we aim to investigate the relationship between worldview and DAS among youth. Aims The aim of this study is to investigate the current state of worldview, psychological flexibility, and DAS in Chinese youth groups, and to explore the relationship between youth worldview, psychological flexibility, and DAS. Methods A total of 2,351 Chinese youths completed questionnaires measuring their worldview, psychological flexibility, and DAS levels. The data were analyzed using structural equation modeling (SEM). Results The impact of youth worldview on DAS was sophisticated. Positive worldview had a negative direct predictive effect on DAS, as well as a negative indirect predictive effect mediated by psychological flexibility. Traditional worldview had a positive direct predictive effect on DAS, a negative indirect predictive effect mediated by psychological flexibility, and a positive total predictive effect. Spontaneous worldview only had positive indirect predictive effects on DAS. Pessimistic worldview had positive direct effects on DAS and indirect effects mediated by psychological flexibility. Policymakers, psychologists, and educators working with youth should carefully consider the implications of these results for education, employment, and mental health.